Evaluating the Efficacy of Platelet-rich Plasma Therapy in Chronic Plantar Fasciitis: A Prospective Study on Pain Relief and Functional Improvement - TM Manohar; P Magesh Babu; S Selvakumar; K Satish Kumar; PS Jayaselvan (Journal of Orthopedics and Joint Surgery)
Introduction: Plantar fascia is a connective tissue structure present on the plantar aspect of the foot, which spans from the calcaneum to the toes. The most common cause of heel pain is plantar fasciitis (PF). PF affects people who are in sports and also middle-aged, obese, inactive people. The peak incidence occurs between 30 and 50 years without gender predilection. Aim and objective: The study aims to assess the functional outcome in patients with PF after platelet-rich plasma (PRP) therapy. Materials and methods: A prospective study involving 20 patients with PF. This procedure consists of preparing PRP after centrifuging 20 mL of venous blood obtained from the patients and injecting it in the heel with the help of a 10 cc syringe. The needle was directed laterally on the plantar surface, just superior and anterior to the calcaneus till it touched the periosteum. Patients are advised to have follow-up visits at 1 week, 2 weeks, 6 weeks, 12 weeks, 6 months, and 1 year post-procedure. Results: Our study shows that PRP injection has a superior outcome in cases of chronic PF that have failed conservative management. In our research, visual analog scale (VAS) score progressively decreased from 7 preop to 2.8 at 6 weeks postop, showing improvement in pain and good functional outcome post-PRP injection. Conclusion: The primary goals in treating PF are pain relief and functional improvement. While conservative treatments like nonsteroidal anti-inflammatory drugs (NSAIDs), ice application, arch support, and physical therapy are common, this study shows that PRP injections offer a promising alternative. PRP not only promotes cell regeneration but also provides sustained pain relief, particularly over 24 weeks. The findings suggest PRP is an effective treatment, especially in degenerative cases, and may be superior to steroid injections for long-term pain management. Further research with larger samples is recommended to confirm these results.